Pengembangan Masyarakat Lokal Melalui Pelatihan homestay untuk meningkatkan daya tarik wisata di balang butung selayar - atik, hamsiati; Sabran, Sabran; Suardana, Wayan (Lembaga Dongan Dosen, 2024)
This study aims to explore the development of local community potential in enhancing tourism appeal through homestay management training in Balang Butung Tourism Village, Selayar Regency. The training, focusing on hygiene, sanitation, and homestay services, has shown positive results with improvements in local residents' knowledge and skills. Active participation in implementing hygiene standards and tourism services has significantly impacted the destination’s quality, potentially increasing tourist visits. Data collection methods included surveys, interviews, and direct observations, which were analyzed using descriptive qualitative methods. The findings highlight that tourism infrastructure development and community involvement are crucial for sustainable tourism development. Therefore, continuous collaboration between the government, community, and private sector is needed to ensure the sustainability of this training program and the improvement of homestay quality